Differences in the Time Allocation Strategy Between Transgenic "Supermice" and Normal Controls and Their Relevance to the Principle of Allocation - Lachman, Edward (My University, 1992)
This study represents the behavioural component of a larger project investigating the life history tactics, physiological resource allocation and behavioural time budgeting of a genetically engineered animal. The "supermouse" is a transgenic strain (mMT-1/rGH) that has one chromosome genetically engineered with extra copies of rat growth hormone genes, each fused to a metallothionein-1 promoter. The GH transgenes are permanently incorporated into the genome of the mouse and are inherited as a block, in a Mendelian manner. "Supermice" exhibit an accelerated growth rate and reach body weights twice that of their normal siblings: both transgenic mice and normal mice are obtained by crossing transgenic males to normal females. Although there must be increased costs associated with achieving their higher growth rate, these: mice show no increases in their specific feeding rates. Consequently there must be a reallocation of resources among various physiological and behavioural demands. The reality of such tradeoffs is known as the Principle of Allocation and predicts that reductions in behavioural activities might be one avenue for realizing extra growth. To test this, six components of the behavioural time budget (resting, locomotion, wheel running, feeding, drinking and grooming) were compared between transgenic and normal mice. Infra-red videocameras recorded the activities of individual male mice in artificial enclosures over 24 hours. The time spent in each bout of activity was recorded and compared. Transgenic mice out-slept their normal counterparts by 126% (an increase of 3.4 h) and were only 53.83% as active in terms of locomotion and wheel running as normal mice. Pooling the data revealed that on average, large mice spent more time at rest and less time engaged in locomotion. Slight but significant decreases in time spent drinking and grooming were also found. Transgenic mice spent only 77.01% as much time drinking, and 69.01% as much time grooming as normal mice. No difference in the amount of time spent feeding was found.
A Time Budget for the Transgenic Supermouse
Keywords: time allocation; supermice; normal control; principle of allocation; transgenic mice; time budget; growth hormone; activity; behaviour; evolution; genetic engineering